Bond Model of Second- and Third-Harmonic Generation in Body- and Face-Centered Crystal Structures. (23rd September 2018) - Hardhienata, Hendradi; Sumaryada, Tony Ibnu; Pesendorfer, Benedikt; Alejo-Molina, Adalberto
Abstract : In this work, we describe the third- and fourth-rank tensors of body- and face-centered cubic systems and derive the s - and p -polarized SHG far field using the simplified bond-hyperpolarizability model. We also briefly discuss bulk nonlinear sources in such structures: quadrupole contribution, spatial dispersion, electric-field second-harmonic generation, and third-harmonic generation, deriving the corresponding fourth rank tensor. We show that all the third- and fourth-rank tensorial elements require only one independent fitting parameter.